Addressing Occupational Dysfunction via Telehealth: A Scoping Review - James T. Foster; Mary Zadnik (International Journal of Telerehabilitation)
Background: This review aims to identify how telehealth was utilized to address occupational dysfunction during the COVID-19 pandemic period. Methods: A scoping review following Arksey and O’Malley’s stages was utilized to explore appropriate research. The scoping review covered articles from January 2020 to December 2022. Results: A total of 23 articles are included in this scoping review which include 15 from the adult age group and eight from the pediatric. Conclusions: The use of telehealth during the COVID-19 pandemic has been shown to improve occupational dysfunction, both within the adult and pediatric settings. Further research is needed to demonstrate the effectiveness of the use of telehealth to address occupational dysfunction.